Implementation of Subsidized Liquefied Petroleum Gas (LPG) Distribution Policy in Kotamobagu City - Mokoginta, Yusmiati; Pangalila, Theodorus; Siwij, Devie S. R. (Technium Social Sciences Journal, 2025)
This study aims to determine and describe the Implementation of Subsidized Liquefied Petrolium Gas (LPG) Distribution Policy in Kotamobagu City along with the supporting and inhibiting factors of the implementation of the policy. This research uses descriptive qualitative methods and data collection techniques through direct observation in the field and interviews. The results showed that the Implementation of Subsidized Liquefied Petrolium Gas (LPG) Distribution Policy in Kotamobagu City as measured by the Provision of Subsidized LPG, Distribution of Subsidized LPG, Subsidized LPG Users and Subsidized LPG Prices has been running well, but there are still some problems found, namely the vacancy of Subsidized LPG stocks at the Sub-Distributor level, Subsidized LPG Distribution that has not been right on target and Subsidized LPG Users who have not been limited based on professional and occupational backgrounds. Supporting factors in the implementation of the Subsidized Liquefied Petrolium Gas (LPG) Distribution Policy in Kotamobagu City are the Subsidized LPG Quota that has been allocated, the existence of Policy Implementers namely the Assignment Business Entity, Distributors and Sub-Distributors of Subsidized LPG, High Retail Price (HET) which has been regulated by the government. While the inhibiting factors are the distribution of subsidized LPG using an open system which results in subsidized LPG being obtained by people from all groups so that it has an impact on the supply of subsidized LPG at the sub-distributor level, the distribution of subsidized LPG that is not on target.